Membrane Stored Curvature Elastic Stress Modulates Recruitment of Maintenance Proteins PspA and Vipp1 - McDonald,C; Jovanovic,G; Ces,O; Buck,M (mBio, 2015)
Phage shock protein A (PspA), which is responsible for maintaining inner membrane integrity under stress in enterobacteria, and vesicle-inducting protein in plastids 1 (Vipp1), which functions for membrane maintenance and thylakoid biogenesis in cyanobacteria and plants, are similar peripheral membrane-binding proteins. Their homologous N-terminal amphipathic helices are required for membrane binding; however, the membrane features recognized and required for expressing their functionalities have remained largely uncharacterized. Rigorously controlled, in vitro methodologies with lipid vesicles and purified proteins were used in this study and provided the first biochemical and biophysical characterizations of membrane binding by PspA and Vipp1. Both proteins are found to sense stored curvature elastic (SCE) stress and anionic lipids within the membrane. PspA has an enhanced sensitivity for SCE stress and a higher affinity for the membrane than Vipp1. These variations in binding may be crucial for some of the proteins’ differing roles in vivo. Assays probing the transcriptional regulatory function of PspA in the presence of vesicles showed that a relief of transcription inhibition occurs in an SCE stress-specific manner. This in vitro recapitulation of membrane stress-dependent transcription control suggests that the Psp response may be mounted in vivo when a cell’s inner membrane experiences increased SCE stress.